Inner Asian polities and their built environment. (September 2017) - Rogers, J. Daniel
Abstract: By 200 BCE the eastern steppe regions centered on Mongolia saw the development of expansive and complex political systems usually referred to as empires. The origins of these polities and the processes of consolidation can be described within the concept of a political community, reflecting the actions of competing groups in expansive social network. For Inner Asia, community was linked to issues of mobility, dispersed control hierarchies, and the economics of multi-resource pastoralism. Together, these patterns offer an alternative vision of the origin and operation of early complex polities. Archaeologically, the pastoralist way of using the built environment provides a window into the dynamics of political processes that operated within a particular polity, but also within multiple polities across long stretches of time. Based on a sample of 76 sites within 13 steppe polities several patterns emerge that highlight how distinctive political processes altered and incorporated community and place in the building of fortified settlements, palaces, military posts, and other constructions. The evidence from these places suggests that these polities operated as inclusive spatial networks that relied more on mobility than the direct interactions seen in urban centers in sedentary societies. The urban centers of the steppe tended to be the byproduct of polity formation, rather than the source.